2013
DOI: 10.1073/pnas.1302721110
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans centriolar protein SAS-6 forms a spiral that is consistent with imparting a ninefold symmetry

Abstract: Centrioles are evolutionary conserved organelles that give rise to cilia and flagella as well as centrosomes. Centrioles display a characteristic ninefold symmetry imposed by the spindle assembly abnormal protein 6 (SAS-6) family. SAS-6 from Chlamydomonas reinhardtii and Danio rerio was shown to form ninefold symmetric, ring-shaped oligomers in vitro that were similar to the cartwheels observed in vivo during early steps of centriole assembly in most species. Here, we report crystallographic and EM analyses sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 31 publications
5
101
0
Order By: Relevance
“…Such a structure could be the underlying reason for the lack of the cartwheel structure in this organism and its replacement by a central tube (Hilbert et al 2013). However, although the detailed arrangements of Sas-6 may vary among different species, its role in dictating centriolar ninefold symmetry seems now indisputable.…”
Section: The Cartwheelmentioning
confidence: 99%
“…Such a structure could be the underlying reason for the lack of the cartwheel structure in this organism and its replacement by a central tube (Hilbert et al 2013). However, although the detailed arrangements of Sas-6 may vary among different species, its role in dictating centriolar ninefold symmetry seems now indisputable.…”
Section: The Cartwheelmentioning
confidence: 99%
“…Here, SAS-6 still defines a nine-fold symmetry, but assembles as a tubular, rather than radial, spiral illustrating how when even using conserved component parts there can be significant evolutionary variation in the mechanisms through which core flagellar structures assemble (Hilbert et al 2013).…”
Section: Origin Of Nine-fold Symmetrymentioning
confidence: 99%
“…X-ray crystallography studies showed that SAS-6 comprises a globular N-terminal domain followed by a long coiled coil ( Figure 1) and a C-terminal disordered region. SAS-6 strongly dimerises in vitro and in vivo via its coiled-coil domain, and protein dimers further interact via their N-terminal domains to form oligomers with 9-fold radial symmetry on average [28][29][30][31]. The SAS-6 N-terminal domain bears strong structural resemblance to similar domains of XRCC4 and XLF (Figure 2), proteins involved in DNA repair and non-homologous end joining.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Caenorhabditis elegans SAS-6 (CeSAS-6) self-assembles into a spiral [30] rather than the planar rings observed in the Chlamydomonas reinhardtii (CrSAS-6; [31]), Danio rerio (DrSAS-6; [29]) and Leishmania major (LmSAS-6; [28]) variants of the same protein. Furthermore, there is substantial heterogeneity in the intrinsic symmetry of SAS-6 oligomers, both inferred by X-ray crystallography and directly visualised by microscopy.…”
Section: Introductionmentioning
confidence: 99%